2017
DOI: 10.2147/ott.s128819
|View full text |Cite
|
Sign up to set email alerts
|

miR-204-5p acts as a tumor suppressor by targeting matrix metalloproteinases-9 and B-cell lymphoma-2 in malignant melanoma

Abstract: An increasing number of microRNAs have been found to be involved in tumorigenesis, including melanoma tumorigenesis. miR-204-5p is down-regulated and functions as a tumor suppressor in many human malignant tumors. miR-204-5p expression is also decreased in melanoma tissues, but its biological roles and molecular mechanisms in malignant melanoma remain unclear. In this study, the aberrant down-regulation of miR-204-5p was detected in melanoma, especially in metastatic melanoma. miR-204-5p also served as a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 33 publications
(42 reference statements)
2
22
0
Order By: Relevance
“…38 Furthermore, Luan et al reportedmiR-204-5p acts as a tumor suppressor by targeting MMP9 and B-cell lymphoma-2 in malignant melanoma. 22 In the present study, our results showed that miR-204 also inhibited cell proliferation and cell migration by targeting MMP9 in CRC cells. In addition, ectopic PlncRNA-1 could partially rescue suppression of the effect of miR-204 on cell proliferation, cell migration behaviors and EMT process in SW480 cells.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…38 Furthermore, Luan et al reportedmiR-204-5p acts as a tumor suppressor by targeting MMP9 and B-cell lymphoma-2 in malignant melanoma. 22 In the present study, our results showed that miR-204 also inhibited cell proliferation and cell migration by targeting MMP9 in CRC cells. In addition, ectopic PlncRNA-1 could partially rescue suppression of the effect of miR-204 on cell proliferation, cell migration behaviors and EMT process in SW480 cells.…”
Section: Discussionsupporting
confidence: 59%
“…Studies have reported that MMP9 was a direct target of miR‐204 in trophoblast invasion and malignant melanoma . To validate whether miR‐204 targets MMP9 in CRC cells, many experiments were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormally expressed miRNAs play an important role in melanoma formation and progression by serving as potential biomarkers and therapeutic targets (35)(36)(37). In the present study, we investigated the expression levels, the exact roles and the regulatory mechanism of miR-326 in melanoma.…”
Section: Discussionmentioning
confidence: 97%
“…Also, miR‐204‐5p has recently been reported to act as tumour suppressor in melanoma, decreasing cell proliferation, migration and invasion, and promoting cell apoptosis in this cancer (Luan et al., ). The same study identified two direct targets of miR‐204‐5p in MMP‐9 and B‐cell lymphoma‐2 (Bcl‐2) protein.…”
Section: Circulating Cf‐mirnas In Cutaneous Melanoma Stagingmentioning
confidence: 99%